Two-Stage Ultraviolet Degradation of Perovskite Solar Cells Induced by the Oxygen Vacancy-Ti4+ States - Ji, Jun; Liu, Xin; Jiang, Haoran; Duan, Mingjun; Liu, Benyu; Huang, Hao; Wei, Dong; Li, Yingfeng; Li, Meicheng (iScience, 2020)
The failure of perovskite solar cells (PSCs) under ultraviolet (UV) irradiation is a serious barrier of commercial utilization. Here, a two-stage degradation process of TiO2-based PSCs is discovered under continuous UV irradiation in an inert atmosphere. In the first decay stage, oxygen vacancy-Ti3+ (Ti3+-VO) transform into active Ti4+-VO trap states under UV excitation and cause photocarrier loss. Furthermore, Ti4+-VO states can convert back into Ti3+-VO states through oxidizing I−, which result in the accumulation of I3−. Sequentially, the rapid decomposition of perovskite accelerated by increasing I3− replaces the photocarrier loss as the dominant mechanism leading to the second decay stage. Then, a universal method is proposed to improve the UV stability by blocking the transformation of Ti3+-VO states, which can be realized by polyethyleneimine ethoxylated (PEIE) modified layer. The optimized devices remain ∼75% of its initial efficiency (20.51%) under UV irradiation at 72 days, whereas the normal devices fail completely. [Display omitted] •A two-stage degradation process of TiO2-based PSCs under continuous UV irradiation•The transformation of Ti3+-VO to Ti4+-VO states is responsible for the UV degradation•A universal method to enhance the UV stability of PSCs was proposed Inorganic Materials; Optical Materials; Materials Chemistry